Eyewitness accounts in 1900 of the Philippine revolution; the Filipino - American War and the U.S. occupation of the Philippines - Sheridan, Richard Brinsley, 1751-1816.; Turot, Henri, 1865- (Manila : Philippines Trademark Pub, 1998)
Contents: The Filipino martyrs: story of the crime of February 4, 1899/ Richard Brinsley Sheridan - - Emilio Aguinaldo, first Filipino President, 1898-1901/ Henri Turot, translated from the French by Pacifico A. Castro
Keywords: Aguinaldo, Emilio , 1869-1964; Philippines -- History -- Revolution, 1896-1898; Philippines -- History -- Philippine American war, 1899-1902